Exploring translation theories - Pym, Anthony (Routledge, 2014)
Exploring Translation Theories' presents a comprehensive analysis of the core contemporary paradigms of Western translation theory. The book covers theories of equivalence, purpose, description, uncertainty, localization, and cultural translation.